Enfrentando Injustiças Epistêmicas: a Corte Interamericana de Direitos Humanos e a abordagem dos estereótipos interseccionais - Porto, Matheus Macedo Lima (2024)
How does the Inter-American Court of Human Rights address epistemic injustices in cases where evidence valuation was based on stereotypes? To tackle this issue, a selection of cases brought before the C ourt's contentious jurisdiction is adopted, along with a framework developed by the Office of the High Commissioner for Human Rights regarding the judiciary's role in addressing entrenched gender stereotypes (2018). The correlation between intersectionality and human rights in a context where judicial decisions are swayed by stereotypes is a subject of specific case law inquiry by the entities comprising the InterAmerican Human Rights System. Specifically, the Court dismantles local judicial arguments grounded in stereotypes, identifies their usage in investigations and trials, and scrutinizes how evidence assessment is often influenced by them. In this dissertation, the concepts of epistemic injustice, developed by Miranda Fricker, and intersectionality, mainly the contributions of Patricia Hill Collins, are used as theoretical and methodological frameworks, respectively. Initially, the dissertation exposes the conceptual elements of epistemic injustice, stereotypes, and intersectionality, elucidating why epistemic injustice is intertwined with the intersectional framework. Subsequently, the cases selected from the model presented are analyzed. For the selection process, all court rulings on the merits until September 2023 were searched in its repository, utilizing a systematic approach that specifically referenced the terms "stereotype" and "intersectional". Our investigation concluded that the Court's utilization of intersectionality manifests in cases involving gender stereotypes, even in conjunction with other stereotypes. Moreover, the court employs two forms of measures to address epistemic injustices: contesting legal arguments founded on stereotypes and determining replacement measures of a structural and transformative nature. The approach to intersectional stereotypes highlights the importance of a comprehensive interpretation of rights, emphasizing their unity and interconnectedness.